PENGARUH LOKASI DAN KUALITAS PRODUK DALAM MENENTUKAN KEPUTUSAN PEMBELIAN DENGAN MEDIASI MINAT BELI TERHADAP SHOWROOM MAHMUD MOTOR DI KABUPATEN SITUBONDO - Wardana, Egho Prastya; Arief, Mohammad Yahya; Fandiyanto, Randika (Fakultas Ekonomi dan Bisnis, 2022)
The purpose of this study is to find out the main picture of consumers who make transactions with two-wheeled motorized vehicles. The population in this study were consumers of the Mahmud Motor Showroom. The sampling technique was determined by random sampling technique. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that the location has a significant positive effect on buying interest, product quality has a significant positive effect on buying interest, location has a positive significant effect on purchasing decisions, product quality has a significant positive effect on purchasing decisions, buying interest has a significant positive effect on purchasing decisions. significantly positive on the purchase decision. The results of the indirect effect hypothesis test indicate that location on purchasing decisions through purchase intention has a significant positive effect, product quality on purchasing decisions through purchase intention has a significant positive effect.